Molecular phylogenetic and historical biogeographical relationships of Laudakia (Squamata: Agamidae) and intraspecific differentiation of L. stoliczkana inferred from mitochondrial DNA sequences - Liang, Qian-Ru; Shi, Lei (Zootaxa, 2024)
The rock lizard genus Laudakia is representative agamid species from the arid zone, and its genus division has not been resolved yet. Laudakia stoliczkana, which occurs in both Xinjiang, China, and the Gobi Altai, Mongolia, is divided into two subspecies, Laudakia stoliczkana stoliczkana and Laudakia stoliczkana altaica, based on morphological differences, but little is known about the molecular genetic differences between the two subspecies. This study reconstructs the phylogenetic tree of Laudakia and analyses molecular differences between two subspecies of L. stoliczkana by DNA barcoding (COI and 16S). Our results show that: (1) Laudakia is monophyletic and the phylogenetic tree is broadly divided into three main branches, namely branch A (L. caucasia and L. stoliczkana), which occurs mainly in Central Asia and the Gobi Altai region to the north, branch B (L. stellio), which occurs in the Middle East, and branch C (L. tuberculata, L. papenfussi, L. himalayana, L. wui, L. stellio), which occurs mainly near the Himalayas; (2) The biogeographic analysis of Laudakia suggests that the genus probably originated at 43.72 Ma (95% confidence interval HPD: 23.53–66.12Ma) and is associated with the uplift of the Tibetan Plateau and the aridification of Central Asias subsequently; (3) Molecular genetic distances and morphological differences support the delimitation of the two subspecies of L. stoliczkana, with divergence between the two subspecies estimated to have occurred at 3.27 Ma (95% confidence interval HPD: 1.58–5.87Ma), in associated with the recent uplift of the Tian Shan Mountains. The results highlight the importance of the uplift of the Central Asian mountains and the Tibetan Plateau for the divergence of Laudakia.